Problems of interaction and identification from concerned parties in innovative projects - V. V. Ilyuk (Путеводитель предпринимателя)
In article, the problems of cross-industry or intra-branch projects on upgrade, reconstruction and innovative updating of productions arising in case of the solution of interstate tasks are considered. The author pays attention to presence of values of the interested participants (stakeholders) of these projects pursuing own aims of these projects which often are not coinciding the purposes of other participants. Development of effective mechanisms and methodology of ensuring activity of the knowledge-intensive innovative companies which are working in group (cluster) and having different beneficiaries and interested persons is offered. Identification of stakeholders is an initial stage of stakeholder management.